2016
DOI: 10.1016/j.kint.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Higher diet-dependent renal acid load associates with higher glucocorticoid secretion and potentially bioactive free glucocorticoids in healthy children

Abstract: Metabolic acidosis induces elevated glucocorticoid (GC) levels. However, the influence of less strong daily acid loads on GCs is largely unexplored. To investigate this, we studied whether higher acid loads in children, fully within the normal range of habitual diets, associate with endogenous GCs. In a specific quasi-experimental design, we examined 200 6- to 10-year-old healthy participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study equally divided to either high or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 58 publications
0
47
0
2
Order By: Relevance
“…One important issue is the causal relationship of NAE and glucocorticoid metabolism. Exogenous acid loads, typically of greater magnitude than the variations observed in the article by Esche et al , 3 increase NAE excretion and stimulate glucocorticoid metabolism. On the other hand, primary increases in glucocorticoid metabolism, as shown in studies using exogenous glucocorticoid administration, increase renal NAE.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…One important issue is the causal relationship of NAE and glucocorticoid metabolism. Exogenous acid loads, typically of greater magnitude than the variations observed in the article by Esche et al , 3 increase NAE excretion and stimulate glucocorticoid metabolism. On the other hand, primary increases in glucocorticoid metabolism, as shown in studies using exogenous glucocorticoid administration, increase renal NAE.…”
mentioning
confidence: 84%
“…3 A previous report from the Dortmund Nutritional and Anthropometric Longitudinally Designed Study showed significant correlation between higher glucocorticoid hormone levels and impaired bone characteristics in children. 6 Thus, one possible extrapolation is that higher dietary acid loads lead to impaired bone formation in children.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…In children, even mild acidosis can elevate glucocorticoid activity [6, 7], contributing to muscle wasting and bone demineralization. Dietary intake of alkali precursors and alkali therapy have been shown to prevent or correct acidosis, attenuate acidosis-related adverse effects and retard CKD progression [7-11].…”
Section: Metabolic Acidosis In Ckdmentioning
confidence: 99%